2001
DOI: 10.1177/08959374010150012301
|View full text |Cite
|
Sign up to set email alerts
|

Technique Sensitivity: Biological Factors Contributing to Clinical Success with Various Restorative Materials

Abstract: Since the 1950s, clinicians have relied on various formulations of Ca(OH)2 to stimulate dentin bridge formation. Various studies (Kozlov and Massler, 1966; Massler, 1967; Brännström, 1978; Cox et al., 1987; Snuggs et al., 1993) have demonstrated that pulp healing and dentin bridging can occur against a pH spectrum of materials. Recent studies (Akimoto et al., 1998; Cox et al., 1998, 1999; Tarim et al., 1998; Kitasako et al., 1999; Hafez et al., 2000) have reported successful pulp healing and dentin bridging us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
(17 reference statements)
0
17
0
3
Order By: Relevance
“…The literature is replete with the finding that if disinfection can be performed effectively, pulp tissue can heal and new dentin bridge will form. 44 Pulp tissue in immature teeth with open apex has larger volume of pulp tissue with a rich blood supply which may explain why it is more potent in defending infection and to heal. Farsi et al found a success rate of 93% with evidence of continued root growth after using MTA as direct pulp capping to treat carious exposure in young permanent teeth.…”
Section: Outcomementioning
confidence: 99%
“…The literature is replete with the finding that if disinfection can be performed effectively, pulp tissue can heal and new dentin bridge will form. 44 Pulp tissue in immature teeth with open apex has larger volume of pulp tissue with a rich blood supply which may explain why it is more potent in defending infection and to heal. Farsi et al found a success rate of 93% with evidence of continued root growth after using MTA as direct pulp capping to treat carious exposure in young permanent teeth.…”
Section: Outcomementioning
confidence: 99%
“…1,2 However, Ca(OH) 2 -based materials have no adhesive properties toward either dentin or overlaid resins, and they provide poor sealing of the exposed site. 3,4 Since their physical properties are low, they are prone to dissolution by acid-etching 5 and demonstrate low durability.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in the case of capping methods using an adhesive system without calcium hydroxide, inadequate hemostasis can cause microleakage by hampering bonding hybridization of the dentin substrate. [1][2][3][4][5] In author's laboratory, direct pulp capping with adhesive resin of human, 6-9 monkey, [10][11][12][13][14][15][16][17] and rat teeth 18,19 consistently employed a combination of 10% sodium hypochlorite (NaClO) gel and alternate irrigation with 6% NaClO and 3% hydrogen peroxide (H 2 O 2 ). These were undertaken to improve dentin bond strength, and to achieve hemostasis, disinfection, and debridement of the exposure site, and irrigation of the internal dentinal tubules.…”
Section: Introductionmentioning
confidence: 99%